Peran pendamping menelan obat (pmo) dalam pencegahan penularan tbc pada keluarga di wilayah kerja puskesmas karang pule: The role of drug administrative in prevention of tuberculosis transmission in families in the working area of puskesmas karang pule - Galyubi, Gaus; Supinganto, Agus; Istiana, Dian (Stikes Wira Medika Bali, 2021)
Introduction: The success of the tuberculosis elimination program through the role of the Companion Swallowing Drugs (PMO) is one strategy to reduce the number of prevention of TB transmission in the family. Purpose: This study aims to determine the role of PMO in preventing transmission of tuberculosis in the family. Methods: This study was descriptive analytic with a cross sectional approach. The number of samples of 25 respondents using a total sampling technique. The data was collected using a questionnaire and documentation. The results of this study indicate (p-value = 0.142) that there is no significant relationship between the role of companion ingesting drugs in the prevention of transmission of tuberculosis to families in PKM Karang Pule. Recommendations that can be given are to provide health promotion activities regarding the impact of tuberculosis transmission on family members.Keywords: Tuberculosis, Role Of Companion Swallowing Drug, Family.